New Insight into the Role of Nitric Oxide Pathways in Pancreas - Buchwalow, Igor (Acta Histochem Cytochem, 2018)
Nitric oxide (NO) is generated by a family of enzymes termed NO synthases (NOS) that convert L-arginine to NO and citrulline. The role of NO as an important biological mediator and recognition of the pathophysiological significance of superoxides/NO interaction has led to an intensive research and development of therapies based on the interception of the NO signaling cascade in the pancreatitis course. However, the presence and localization of the NO-generating enzymes in various organs including pancreas are subject to controversy. We assumed that this controversy might reflect rather the diversity of experimental approaches and an insufficient sensitivity of the methods used. Applying tyramide signal amplification (TSA) immunohistochemical technology, we were able detect all three NOS isoforms both in exocrine and endocrine compartments and in the vasculature in the normal pancreas and in pancreatitis. This also allowed us to demonstrate that oxidative stress runs ahead of NOS up-regulation, which implies that the NO enhancement in the course of pancreatitis is likely to be an adaptive mechanism aimed at maintaining the homeostatic cellular level of the bioactive NO. The aims of this minireview are to describe normal intrapancreatic NO pathways and the role of NO in the pancreatitis course.